PENGARUH PERTUMBUHAN ASET, PERTUMBUHAN PENJUALAN, PROFITABILITAS, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP PENGARUH PERTUMBUHAN ASET, PERTUMBUHAN PENJUALAN, PROFITABILITAS, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP DEBT TO TOTAL ASSET PADA PERUSAHAAN PEMBIAYAAN YANG TERDAFTAR DI BEI TAHUN 2010 – 2013 DEBT TO TOTAL ASSET PADA PERUSAHAAN PEMBIAYAAN YANG TERDAFTAR DI BEI TAHUN 2010 – 2013 - Tri Wahyono (Jurnal Ilmiah Manajemen dan Bisnis, 2015)
The main purpose of this research was to determine whether the variable asset growth, sales growth,profitability, and firm size are considered to affect the debt to total asset by a variety of literature andprevious research. The sampling method use purposive sampling. Tecnique of data analysis use multiplelinear regression analysis by pooling the data. The results showed that five independent variablessimultaneously significant effect on debt to total asset with F score 19,132 and probability score 0,000, less than significantcy score 0,05. The asset growth and sales growth does not influence has a positive andsignificant influence on debt to total asset, while profitability has a negative influence on debt to total asset.Meanwhile, two other variables, liquidity and business risk has a positive and significant influence debt tototal asset.The main purpose of this research was to determine whether the variable asset growth, sales growth,profitability, and firm size are considered to affect the debt to total asset by a variety of literature andprevious research. The sampling method use purposive sampling. Tecnique of data analysis use multiplelinear regression analysis by pooling the data. The results showed that five independent variablessimultaneously significant effect on debt to total asset with F score 19,132 and probability score 0,000, lessthan significantcy score 0,05. The asset growth and sales growth does not influence has a positive and significant influence on debt to total asset, while profitability has a negative influence on debt to total asset.Meanwhile, two other variables, liquidity and business risk has a positive and significant influence debt tototal asset.